Revolution in Fable Universe: Introducing Technology in Children's Literature - Setiawan, Rahmat; Andanty, Ferra Dian; Kinasih, Titah; Kurnia, Meytha Dwi; Doyat, Dolmat (The Study Program of English Education of Palangka Raya University, 2025)
This research explores the integration of technology into fable narratives as a means of introducing digital literacy to children, thus, it aims at investigating the perspectives of three experienced literature lecturers on how technology can be embedded within fable stories, focusing on narrative structure and moral conflicts. Employing a qualitative research design with a narrative approach, data were collected through in-depth interviews with literature. Thematic analysis was used to interpret the findings. Results reveal a shared view that technology should not merely serve as a narrative backdrop but should catalyse critical reflections on ethical, social, and personal dimensions of digital life. Fables are seen as an adaptable medium to instil both traditional values and modern critical thinking about technology. The study concludes that technologically infused fables have the potential to enrich children’s literature, balancing aesthetic integrity with the demands of digital literacy. It is suggested that future research expands into creating and testing specific fable models within educational settings. Keywords: Fable, Technology, Children’s Literature, Digital Literacy